EFEKTIFITAS TREATMENT BRAST CARE UNTUK MEMPERLANCAR PRODUKSI ASI DI WILAYAH KERJA PUSKESMAS BARUGA - Sumarni; Husnul Khatimah; Atika Sulastri; A. Nurhikma Dea Oktavia (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2019)
Mother's Milk (ASI) is one of the most important parts where the production and its smoothness need to be considered by prospective mothers. So many benefits that will be obtained for the mother and of course for the baby. To ensure the implementation of breastfeeding, the Government of Indonesia has regulated by making an official regulation, namely Government Regulation (PP) No. 33 of 2012. The purpose of this study is to determine the effectiveness of the Brast Care Treatment to facilitate milk production in the work area of ??the Baruga Health Center. The design of this research is an analytical survey with a cross sectional approach, namely research that tries to explore how and why this phenomenon occurs. Based on the results of statistical tests with Chi-Square obtained p value of 0.004 (p < 0.05), which means that Brast Care Treatment is effective in increasing breast milk production.